Problems of increasing the efficiency of the parliamentary control mechanism in the Republic of Kazakhstan - Taitorina, B.A.; Abdukarimova, Z.T.; Beisenbayeva, M.T.; Bogatyreva, L.B. (Bulletin of the Karaganda University “Law Series”, 2020)
The article analyzes the problems of organizing parliamentary control in the Republic of Kazakhstan.Based on the analysis of modern research in the Republic of Kazakhstan and foreign countries, relevant issues of the formation and development of this legal institution have been raised. The authors of the article substantiated conceptual provisions. Parliament has a complex multifunctional mechanism for effective control. The analysis is based on two fundamental conceptual principles in the interpretation of parliamentary control. Firstly, parliamentary control as a system of norms aimed at checking and evaluating the activities of executive bodies, with the possible application of sanctions. Secondly, parliamentary control is a set of measures that allows initiating the resignation of the government. The principle of democracy is the initial category of parliamentarism. The central category of parliamentary law theory is the principle of separation of powers. The main functions of the Parliament are updated: legislative, representative, control. The article formulates the main conclusions and presents options for improving the effectiveness of the mechanism of parliamentary control in the Republic of Kazakhstan. One of the main conclusions of the study is the conclusion that a law is needed in the republic that would regulate and intensify the activities of the Parliament in such aspects as appeal to procedural forms of control such as interpellation with its ability to apply political sanctions, a resolution of censure, a parliamentary investigation of official crimes persons entailing their resignation, etc.